Exploring the Impact of Smart Tourism Initiatives on Digital Native's Travel Behavior: A Review - Goeltom, Andar Danova Lastaripar; Hurriyati, Ratih; Gaffar, Vanessa; Wibowo, Lili Adi; Susanto, Eko (Business Education Program of Universitas Pendidikan Indonesia, 2024)
Digital technology has revolutionized the tourism sector, leading to the emergence of digital-native tourists who prefer tech-savvy experiences. Smart tourism initiatives leverage information and communication technologies to offer personalized and interactive experiences, aligning with the preferences of digital natives. This study employs a literature review approach to explore the influence of smart tourism on the travel behavior of digital native tourists. Findings reveal a significant research gap in understanding how smart tourism initiatives specifically resonate with digital native behaviors. Digital natives, characterized by their digital fluency, exhibit distinct preferences influenced by their immersion in technology. Smart tourism technologies are crucial in predicting digital natives' destination choices and visit intentions. Understanding this dynamic is crucial for the tourism industry to meet the evolving needs of digital native tourists. Leveraging innovative technologies and tailored strategies can enhance visitor satisfaction, operational efficiency, and sustainability in the tourism sector, ultimately shaping the future of smart tourism experiences.